2016
DOI: 10.1159/000442280
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lowering Haemoglobin Targets on Patterns of Erythropoiesis-Stimulating Agent Use in Patients on Haemodialysis

Abstract: Background/Aims: Haemoglobin (Hb) targets have been reduced in patients receiving haemodialysis (HD). We have investigated the impact of new guidance on current practices and costs. Methods: Anaemia management in all patients undergoing thrice-weekly HD was retrospectively reviewed. Hb targets were compared against Kidney Disease: Improving Global Outcomes 2012 recommendations. The impact of new guidance was assessed by comparing anaemia parameters pre- and post-guideline publication. Results: Two hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Table 1 presents the characteristics of the included studies. Study designs included four (26.7%) RCTs [46][47][48][49] , four (26.7%) retrospective studies [50][51][52][53] , three (20.0%) simulation studies [54][55][56] , two (13.3%) cross-sectional surveys 57,58 , and two (13.3%) prospective single-arm trials (Figure 2) 59,60 . Six (40.0%) studies were real-world studies (non-simulated, noninterventional) [50][51][52][53]57,58 , including three (50.0%) 51,57,58 published after 2012.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 presents the characteristics of the included studies. Study designs included four (26.7%) RCTs [46][47][48][49] , four (26.7%) retrospective studies [50][51][52][53] , three (20.0%) simulation studies [54][55][56] , two (13.3%) cross-sectional surveys 57,58 , and two (13.3%) prospective single-arm trials (Figure 2) 59,60 . Six (40.0%) studies were real-world studies (non-simulated, noninterventional) [50][51][52][53]57,58 , including three (50.0%) 51,57,58 published after 2012.…”
Section: Search Resultsmentioning
confidence: 99%
“…Study designs included four (26.7%) RCTs [46][47][48][49] , four (26.7%) retrospective studies [50][51][52][53] , three (20.0%) simulation studies [54][55][56] , two (13.3%) cross-sectional surveys 57,58 , and two (13.3%) prospective single-arm trials (Figure 2) 59,60 . Six (40.0%) studies were real-world studies (non-simulated, noninterventional) [50][51][52][53]57,58 , including three (50.0%) 51,57,58 published after 2012. Two publications were derived from the same study (included the same patients), but reported different results (different HRQoL instruments were used) 47,48 .…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations